МАРКАЗИЙ ОСИЁ МАМЛАКАТЛАРИ ТАРИХИДА ЖИСМОНИЙ МАДАНИЯТНИНГ ТУТГАН ЎРНИ - Жумакулов, З.П. (SCIENCE and SOCIETY, 2022)
The paper studies statehood of Central Asian countries. Defining the role and values of physical culture and military training in social economic developments of the Central Asia’s governments.
Keywords: hunting; hunting equipments; battles; weapon; tribes; tribal (clan) society; primitive society; physical and military training of the population and youth; national traditions; customs competitions